Trends in Vigorous Physical Activity Participation Among Ontario Adolescents, 1997–2001 - Irving, Hyacinth M. (Can J Public Health, 2003)
OBJECTIVE: This paper examines trends in vigorous physical activity participation among students enrolled in grades 7, 9, 11 and 13 in Ontario between 1997 and 2001. Patterns in participation by gender and grade level are also described. METHODS: Data were derived from the Ontario Student Drug Use Survey for 1997, 1999, and 2001. Three outcomes of vigorous physical activity were included in self-report questionnaires completed by more than 5,000 students over a three-year period. They responded to the survey in classroom groups during school time. Estimates were weighted and variance and statistical tests have been corrected for the complex sample design. RESULTS: Comparisons between 1997 and 2001 indicated that, overall, patterns of vigorous physical activity remained stable. However, there were significant declines in vigorous physical activity participation by females and 11th grade students between 1997 and 2001. INTERPRETATION: The trends for females and 11th graders are disturbing, since they indicate that the normal gender and age differences in vigorous physical activity participation, found in numerous previous studies, are compounded by declining levels over time for these groups.